Charakterystyka stratyfikacji termicznej i chemicznej wód jeziora Ostrowite (PNBT) w roku 2015 = Features of the thermal and chemical stratification of the Ostrowite Lake water in the year 2015 - Gierszewski, Piotr; Miler, Karol; Kaszubski, Michał (Journal of Education, Health and Sport, 2015)
Gierszewski Piotr, Miler Karol, Kaszubski Michał. Charakterystyka stratyfikacji termicznej i chemicznej wód jeziora Ostrowite (PNBT) w roku 2015 = Features of the thermal and chemical stratification of the Ostrowite Lake water in the year 2015. Journal of Education, Health and Sport. 2015;5(12):217-229. ISSN 2391-8306. DOIhttp://dx.doi.org/10.5281/zenodo.35354 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%2812%29%3A217-229 http://pbn.nauka.gov.pl/works/679838 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011–2014http://journal.rsw.edu.pl/index.php/JHS/issue/archive Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 10.11.2015. Revised 25.11.2015. Accepted: 14.12.2015. Charakterystyka stratyfikacji termicznej i chemicznej wód jeziora Ostrowite (PNBT) w roku 2015 Features of the thermal and chemical stratification of the Ostrowite Lake water in the year 2015 Piotr Gierszewski1, Karol Miler1, Michał Kaszubski2 1. Instytut Geografii, Uniwersytet Kazimierza Wielkiego w Bydgoszczy 2. Instytut Geografii i Przestrzennego Zagospodarowania, Polska Akademia Nauk Abstrakt W artykule przedstawiono problem zróżnicowania stratyfikacji termicznej i chemicznej wód w wieloakwenowym jeziorze Ostrowite położnym na obszarze Parku Narodowego „Bory Tucholskie”. Na podstawie pomiarów temperatury, koncentracji tlenu rozpuszczonego w wodzie i wartości przewodnictwa elektrolitycznego wody w okresie wiosennej cyrkulacji i letniej stagnacji wykazano różny charakter stratyfikacji wód w poszczególnych akwenach jeziora. Określono, że największym indywidualizmem pod tym względem charakteryzowała się wschodnia rynna jeziora. Ze względu na wielkość oraz cechy morfometryczne ta część jeziora wykazywała mniejszą dynamikę wód. Słowa kluczowe: jezioro dymiktyczne, stratyfikacja wód, zróżnicowanie temperatury wody, koncentracja tlenu, przewodnictwo elektrolityczne, jezioro Ostrowite. Abstract The paper presents the problem of the diversity of thermal and chemical stratification in the multi-pools Ostrowite Lake, situated on the area of the National Park "Tucholskie Forests". Based on measurements of temperature, dissolved oxygen concentration in water and the electrolytic conductivity of water conducted during spring turnover and summer stagnation of water, the diversity of water stratification in various pools of the lake has been shown. The greatest individuality due to the course of stratification, was occurred in the western channel of the lake. Taking into account the size and morphometric parameters, this part of the lake revealed a lower dynamic of water. Key words: dimictic lake, water stratification, water temperature diversity, oxygen concentration, electrolytic conductance, Ostrowite Lake.